Ran promotes membrane targeting and stabilization of RhoA to orchestrate ovarian cancer cell invasion - Kossay Zaoui (Nature Portfolio, 2019)
Ran, a nucleus-cytoplasm shuttle protein, is implicated in cancer development and survival. Here, the authors show that Ran binds RhoA to impair its degradation and allow its localisation to the plasma membrane of ovarian cancer cells for tumour invasion.